Cardiovascular risk factors in a population attending a community event on health education - Coltro, Rodrigo Soler [UNESP]; Mizutani, Bruno Moreira [UNESP]; Mutti, Anibal [UNESP]; Délia, Maria Paula Barbieri [UNESP]; Martinelli, Luiz Mário Baptista [UNESP]; Cogni, Ana Lúcia [UNESP]; Matsubara, Beatriz Bojikian [UNESP] (Elsevier, 2009)
IntroductIon. Cardiovascular diseases (CVD) are the main cause of death in Brazil. objectIve. To evaluate the frequency of CVD risk factors in a population attending a health education community event. Methods. Retrospective study that included 428 completed forms with clinical and demographic information of volunteers attending a public event, in May, 2006. Data were expressed by means and standard deviation or proportions and compared by Student ́s t test or Chi-square test. Associations between Arte-rial Hypertension (AH), Diabetes Mellitus (DM) and clinical variables were analyzed by multinomial logistic regression. Significance level was p <0.05. Results. Mean age was 57±14 years, and women represented 58% of the total population. The main cardiovascular risk factors were AH (39.5%), DM (15.4%) and dyslipidemia (25.8%). The frequency of unawareness about these risk factors was respectively 8.4%, 17.5% and 33.1%.. Family history of CVD was reported by 41% while only 67% reported having any information about DM or dyslipidemia. Among obese individuals (IMC≥30 Kg/m2, 27.3% of the population), systolic blood pressure (133±16mmHg), diastolic blood pressure (84±11.5mmHg) and casual glycemia (124±52.5mg/dl) were higher when compared to non-obese (p<0.05). There was a significant association between obesity and dyslipidemia (p=0.04). Age and IMC were independently associated with AH and DM. conclusIon. The high frequency of modifiable cardiovas-cular risk factors in this population suggests the need for educational programs to promote primary prevention, mainly for the elderly and overweight.
Frequênci a de fatores de risco cardiovascular em voluntários partici pantes de evento de educação em saúde
Keywords: Arterial hypertension; Community population; Diabetes mellitus; Obesity; Risk factors